Perception on community capacity, engagement, and participation among urban refugee children at community-based schools in Klang Valley, Malaysia - Ang, Peng Hoe (2016)
The community being researched on in this study are children of urban refugee dwellers attending primary level education in Klang Valley, Malaysia. As education for refugees in Malaysia is outside the ambit of the national education system, refugee children do not have access to national primary level education institutions. This research seeks to specifically describe community-based schools located in the Klang Valley, and the respondents of these schools. On top of that, the research will also determine the levels of student engagement (comprising of behavioural, emotional and cognitive engagement), the types of participation (voluntary and involuntary), the levels of participation (student attendance), the levels of perception and the levels of community capacity in English literacy skill and knowledge (student achievement) of the respondents at the community-based school. Subsequently the research examines the relationship between student engagement, level of participation and the level of perception with level of community capacity. The research also compares the difference between the types of participation with level of community capacity and examines the relationship between the student‟s age and the number of years in school (duration of participation) with level of community capacity. Finally the research seeks to determine the unique predictors of community capacity among urban refugee children living in Klang Valley. The study design was approached quantitatively using survey questionnaires with a small descriptive portion of the study utilising qualitative approaches of informal interviews and participant observation. The study was carried out at the United Nations High Commissioner for Refugee (“UNHCR”) recognised schools of El Shaddai Refugee Learning Centre (“ERLC”), and the Chin‟s Children Education Centre (“CCEC”), both being community-based schools located at Klang Town and Sungei Besi respectively. The sample size of the respondents from both these community-based schools is 241, out of a combined population of 499 refugee students. The findings of this study indicated that student engagement and students‟ level of participation had a positive correlation to community capacity. Upon analysing the differences between the types of participation (involuntary and voluntary) in relation to community capacity, the results show that there is no significant difference to report in this comparison. Further analysis also shows that there is no significant relationship between the respondents‟ level of perception in learning English, their age as well the number of years they have been in ERLC and CCEC with their community capacity. When the correlated predictors were regressed against community capacity, both level of participation and emotional engagement were the most significant predictor variables.Therefore this study shows that refugee students who are attending community-based schools, and who are emotionally engaged, have a higher tendency to develop community capacity, as seen in their achievement of better grades in their English Language Literacy assessment.